Understanding and Identifying Bullies in Al-Ishlahiyah Singosari Integrated Vocational School - Rahmafridaya, Salsa; Bilkist, Inacio Imelda Dewi; Fadhil, Rizqi; Simon, Irene Maya; Hasanah, Laili Uswatun; Pratiwi, Awalya Siska (Proceedings Series of Educational Studies, 2024)
The widespread occurrence of bullying in schools today can have negative impacts and cause serious problems for the mental and academic well-being of both victims and perpetrators. This study aims to identify the perpetrators and victims of bullying at SMK Terpadu Al-Ishlahiyah Singosari and to strengthen programs for prevention and intervention. The research employs a descriptive quantitative method using the "No Bullying" application to collect sociometric data from 125 tenthgrade students across four vocational tracks. The sociogram results were analyzed using descriptive analysis techniques. The findings indicate that most tenth-grade students at SMK Terpadu AlIshlahiyah Singosari have either engaged in bullying or are currently involved in bullying. In each class, there are several students who have been reported by their classmates as perpetrators of bullying. This suggests that both male and female students have an equal tendency to bully their classmates. Additionally, there are several factors that may cause students to act as bullies. Based on these findings, bullying remains a serious issue at SMK Terpadu Al-Ishlahiyah Singosari. Keywords: bullying; identification; sociogram